The Effectiveness of Corruption Law Enforcement in Providing a Determinant Effect on the Performers - Dian Adriawan (Budapest International Research and Critics University, 2022)
The existence of Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, directly or indirectly, is expected to suppress leakage and irregularities in the state's finances and economy. By anticipating these deviations as early and as much as possible, it is hoped that the wheels of the economy and development can be carried out properly. However, ironically, the more intensive efforts to eradicate corruption have not led to a decrease in the number of corruption crimes in Indonesia. The purpose of this study was to determine the effectiveness of criminal sanctions given to defendants of corruption. The research method is carried out by examining library materials or secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials. The professionalism of the judge's decision is very decisive in providing a deterrent effect to the perpetrators of criminal acts of corruption so that, only with an effective judge's decision can corruption be stopped or at least reduced. Moreover, the law has very firmly given the threat of the heaviest punishment, namely the death penalty to anyone who commits a criminal act of corruption that is detrimental to state finances, now how judges can implement the existing law through decisions that fulfil a sense of justice.